Effects of Production System With or Without Growth-Promoting Technologies on Growth and Blood Expression of (Cyto)Chemokines and Heat Shock and Tight Junction Proteins in Bos taurus and indicus Breeds During Summer Season - Mark Branine; Ashley K. Schilling-Hazlett; Pedro H. V. Carvalho; Kim R. Stackhouse-Lawson; Edilane C. Martins; Julia T. da Silva; Laura Amundson; Chris Ashworth; Mike Socha; Sami Dridi (Veterinary Sciences)
Heat stress (HS) induced by global warming is a real welfare, productivity, and economic burden of cattle production. However, some cattle breeds have superior physiological adaptive traits to others, yet the underlying molecular mechanisms are not fully defined. The present study aimed, therefore, to determine the expression profile of stress-related molecular signatures in the blood of thermosensitive Angus (Bos taurus) and thermotolerant Brahman (Bos indicus) cattle breeds managed without (CON) or with growth-promoting technology (TRT) during the summer (April–October, 2023) season in Colorado, US. Body weight (BW) was significantly increased from April to October, and the amplitude was greater for the Angus compared to the Brahman breed. The TRT system slightly increased BW, mainly in the Angus breed. Molecular analyses showed that all tested genes were expressed in beef cattle blood. When comparing production systems, the expression of HSP1A1 was significantly upregulated, and HSP90 was downregulated in CON compared to TRT cattle. The expression of IL6, CCL20, and OCLN was induced by the CON system only in the Angus and not in the Brahman breed. At the breed level, Angus cattle exhibited greater expression of IL10, CCL20, and CLDN1 compared to their Brahman counterparts. There was a significant period by production system as well as period by breed interactions. The expression of HSP1A1 increased in both breeds during October. The expression of IL10, CXCL14, CXCR2, and CLDN1 was affected by the production systems in a period-dependent manner. However, the expression of IL6, CXCL14, CCL5, and CXCR2 was upregulated in Angus cattle in a period-sensitive manner. In summary, HSPs, (chemo)cytokines, and tight junction proteins are expressed in the whole blood of beef cattle, and their expression is regulated in a breed-, period-, and/or production system-dependent manner. This could open new vistas for future research to identify molecular signatures for non-invasive stress monitoring and/or marker-assisted genetic selection for robustness and resilience to HS.